Multiple congenital malformations of Wolf-Hirschhorn syndrome are recapitulated inFgfrl1null mice - Catarina Catela; Daniel Bilbao; Esfir Slonimsky; Paschalis Kratsios; Nadia Rosenthal; Pascal te Welscher (2009)
Wolf-Hirschhorn syndrome (WHS) is caused by deletions in the short arm of chromosome 4 (4p) and occurs in about one per 20,000 births. Patients with WHS display a set of highly variable characteristics including craniofacial dysgenesis, mental retardation, speech problems, congenital heart defects, short stature and a variety of skeletal anomalies. Analysis of patients with 4p deletions has identified two WHS critical regions (WHSCRs); however, deletions targeting mouse WHSCRs do not recapitulate the classical WHS defects, and the genes contributing to WHS have not been conclusively established. Recently, the human FGFRL1 gene, encoding a putative fibroblast growth factor (FGF) decoy receptor, has been implicated in the craniofacial phenotype of a WHS patient. Here, we report that targeted deletion of the mouse Fgfrl1 gene recapitulates a broad array of WHS phenotypes, including abnormal craniofacial development, axial and appendicular skeletal anomalies, and congenital heart defects. Fgfrl1 null mutants also display a transient foetal anaemia and a fully penetrant diaphragm defect, causing prenatal and perinatal lethality. Together, these data support a wider role for Fgfrl1 in development, implicate FGFRL1 insufficiency in WHS, and provide a novel animal model to dissect the complex aetiology of this human disease.